The Existence of Pragmatic Markers in Americas’ Got Talent Judges’ Commentaries - Naben, Maria Fridolin; Mujiyanto, Januarius; Faridi, Abdurrachman (English Education Journal, 2019)
This study attempts to explain the use of pragmatic markers in Americas’ Got Talent judges’ commentaries. The aims of the study are to analyze the existence of verbal and visual pragmatic markers and explain their relationship. The verbal pragmatic markers are categorized into four types based on the typology of pragmatic markers proposed by Fraser (1996). They are basic markers, commentary markers, parallel markers, and discourse markers. While the visual pragmatic markers divided into thinking face, pointing with gaze and hand movement and smile following the pragmatic function facial gestures from Bavelas & Chovil (2013). This research employed descriptive method with qualitative approach. The object of the study is judges of Americas’ Got Talent season 13 which consist of Simon Cowell, Heidi Klum, Mell B, and Howie Mendel. The study revealed that the judges used the basic markers to express the main message of the comment, commentary markers to express the message contains in the comment toward the main message, parallel markers to express the complement message toward the main message and the discourse markers to express the relation between the main message and the other utterance. The visual pragmatic markers performed also signals certain message related to verbal markers. The judges performed the thinking face to signal the word search, pointing with gaze and hand movement to emphasize the messages convey in utterance and smile to signal pleasure. This research could provide an understanding of EFL learners in using pragmatic markers as a way to improve communication strategy in communication.